Effect of Various Postproduction Heat Treatment on Lipid Composition and Oxidation in Chinese Nanjing Salted Duck - Dai, Yan; Liu, Deng‐Yong; Chen, Ming; Lei, Yun; Zhai, Ya‐Nan; Xu, Xing‐Lian; Zhou, Guang‐Hong (Journal of food processing and preservation, 2014)
Traditional Nanjing salted ducks are cooked at low temperatures. However, factories in China that attempt to mass produce this meat require a heat‐treatment stage to maintain the safety of this food product over longer storage periods. Conjugated diene, carbonyl, thiobarbituric acid‐reactive substances, peroxide, and the compositions of fatty acids (FA) and triacylglycerols (TGs) were measured in Chinese Nanjing salted ducks following different heat treatments including a control, 99C, 108C, microwave and 121C heat treatments after packaging. Heat treatments increased (P < 0.05) carbonyl and peroxide values and the percentages of C18:2n6, C18:3n3, C20:4n6, polyunsaturated FAs, unsaturated FA and some TGs; however, heat treatments decreased (P < 0.05) C16:0, C16:1, C18:1, monounsaturated and saturated fatty acids, and other TG fractions in the duck meat especially after microwaving or being treated at 121C. Further research should explore modifying current preservation methods to improve meat quality. PRACTICAL APPLICATIONS: Heat treatment of packaged products is considered an effective method of increasing their shelf life. However, such treatment can also distort the flavor of products, largely because of lipid oxidation. This study investigated changes in lipid composition and oxidation in heat‐treated ducks to indirectly explore the mechanism behind off‐flavor formation.